Simulation of Urban Growth in Ternate Island using Cellular Automata Markov Chains Models - Rakuasa, Heinrich; Khromykh , Vadim V. (CV. Science Tech Group, 2025)
Ternate Island is part of the administrative area of Ternate City, North Maluku Province which was once the capital of the province and the center of government continues to experience physical development. This study aims to analyze the development of urban growth in Ternate Island in the period 2004-2032. The cellular automata markov chain method uses 2004, 2014 and 2024 land cover data and driving factors consisting of elevation, slope, distance from road and distance from POI to predict urban growth. The results of the analysis show that the urban area continues to increase in area, namely in 2004 the urban area had an area of 1,424.14 ha, 2014 an area of 1,728.45 ha and in 2024 an area of 2,010.78. The prediction results of urban growth on Ternate Island in 2032 show that the urban area has an area of 2,884.37 ha. Based on the research results from the application of the markov chain cellular automata method, it is hoped that these findings can be taken into consideration in designing a sustainable spatial arrangement of Ternate City. So that ecological balance, environmental balance and food security can be maintained and meet the requirements of a city that has the carrying capacity and environmental capacity.